2014
DOI: 10.1186/1756-0500-7-599
|View full text |Cite
|
Sign up to set email alerts
|

Awareness regarding risk factors of type 2 diabetes among individuals attending a tertiary-care hospital in Bangladesh: a cross-sectional study

Abstract: BackgroundAwareness regarding risk factors is a prerequisite for the prevention of diabetes in general population. However, there are great variations in the level of this awareness from population to population and this needs to be explored in different ethnic and social groups for designing appropriate preventive strategies. The purpose of the study was to assess the level of awareness regarding the risk factors responsible for the development of type 2 diabetes and its determinants among individuals who att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 20 publications
10
42
3
Order By: Relevance
“…18 In a similar study it was observed that the two most important sources were friends & neighbor (51%) and family (49%) respectively, followed by electronic media (46%) whereas in our study it was almost by the healthcare provider. 19 Ying et al in their study also had finding similar to our study and they also concluded that the main strategy is patients education about the complications. 20 Nearly all the patients were on some form of medications for the treatment of diabetes.…”
Section: Discussionsupporting
confidence: 88%
“…18 In a similar study it was observed that the two most important sources were friends & neighbor (51%) and family (49%) respectively, followed by electronic media (46%) whereas in our study it was almost by the healthcare provider. 19 Ying et al in their study also had finding similar to our study and they also concluded that the main strategy is patients education about the complications. 20 Nearly all the patients were on some form of medications for the treatment of diabetes.…”
Section: Discussionsupporting
confidence: 88%
“…[8,12] Similar study by Vankudre et al in Kanchipuram district showed a significant difference in awareness scores with the marital status (mean score of 37.3 ± 5.98). [13] Among the participants who were aware of the symptoms, 18.1% knew about polyuria, and among the diabetics, 45.3% were aware of it followed by 35.9% of the diabetics were aware of polydypsia, 23.4% of polyphagia, and 15.6% of them knew about unexplained weight loss.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, in the present study, 54% of the subjects were scored average, 42.5% scored poor and the remaining 3.5% scored good on awareness of diabetes. [12] …”
Section: Discussionmentioning
confidence: 99%
“…While few other studies remarked on variations in the knowledge of DM among participants (Fezeu, Fointama, Ngufor, Mbeh & Mbanya, 2010;Mahajerin, Fras, Vanhecke & Ledesma, 2008). Deepa et al (2014), Mumu, Saleh, Ara, Haque, & Ali (2014) and Ulvi, et al (2009) found that the majority of participants were unaware of the associated risk factors. Contrary findings were found in the study by Wee, Ho, & Li (2002).…”
Section: Knowledge About Dmmentioning
confidence: 99%